A study of correlation of pre-operative hearing status and intraoperative ossicular findings in mucosal chronic otitis media - Parmar, Maitri; Khilnani, Ajeet K.; Hirani, Narendra; Sorathiya, Rashmi; Tank, Ayush; Chaudhary, Raj (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2026)
Background: Mucosal chronic otitis media (COM) is a common cause of hearing loss due to tympanic membrane perforation and middle ear pathology. Preoperative audiometry helps assess hearing impairment, but it may not always correlate with intraoperative finding. This study was conducted to assess the correlation between pre-operative hearing status and intra-operative findings, particularly, in patients undergoing tympanoplasty. Methods: This prospective study has been conducted in patients presenting with mucosal type of COM in Otorhinolaryngology- Head and Neck Department of GKGH, GAIMS, Bhuj from the period of June 2023 to September 2024. All patients with mucosal COM without any intracranial complications were included in the study. Pre-operative and post-operative pure tone audiometry (PTA) threshold and Intra-operative findings were recorded and analysed using Microsoft Excel sheets. Results: A total of 111 patients with clinically diagnosed mucosal-type chronic otitis media were included. The mean age of patients was 33.66 years, with a female predominance (64.9% female, 35.1% male). The majority of patients (41%) were in the 21–30-year age group. Comparison of preoperative and 3-month postoperative pure-tone average (PTA) demonstrated a statistically significant improvement in hearing levels following surgery. Graft uptake was successful in 98.2% of patients at 3 months postoperatively, with only 1.8% showing residual perforation. Conclusion: Pre-operative hearing assessment, particularly through PTA thresholds, serves as a valuable predictor of intra-operative ossicular chain status. Tympanoplasty is an effective surgical intervention, leading to significant hearing improvement in patients with mucosal CSOM. Early diagnosis and intervention are crucial in preventing further ossicular damage and optimizing surgical outcomes.